Toxicity of Heavy Metal Hg (Mercury) and Sublethal Test to Pangasius hypophtalmus - Eka Sandra Bayu; Syafriadiman '; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research of toxicity of Heavy Metal Hg (Mercury) and Sublethal Test to Pangasius hypophtalmus has been conducted on October to November 2016 in Laboratory of Environmental Quality Cultivation of the Faculty of Fisheries and Marine University of Riau. The objective of this research were measured the concentrations of toxicity for Pangasius hypophtalmus in short time period in controlcondition. In this study, static 96-h acute toxicity test were carried out using Pangasius hypophtalmus as test organisms. Probit analysis using the computer software EPA and graphical method were used to calculate the 96-h LC50 depending on data suitability. Result of the 96-h LC50 and Biological Safety Level of heavy metal Hg were 0,201 mg/L and 0,00201 mg/L. The increase of heavy metal Hg (Mercury) concentrations can be low the absolute growth rate and daily of the Pangasius hypophtalmus larvaeKeywords : Toxicity, Mercury, Sublethal, Pangasius hypophtalmus.